Heat-resistant anti-freezing water-based permeable inorganic waterproof agent as well as preparation method and application thereof

By using modified silica and specific dispersant compositions in water-based permeable inorganic waterproofing agents, the problem of insufficient adaptability and stability of existing waterproofing agents in extreme environments and deep work is solved, and better waterproofing performance and durability are achieved.

CN119613077AActive Publication Date: 2025-03-14HEFEI OAK TREE INSECT CREATIVE DESIGN CO LTD

Patent Information

Application Number
CN202411960934.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-14
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The existing water-based permeable inorganic waterproofing agents are insufficient in adaptability and stability under extreme climate conditions, and have poor penetration depth and pore filling effects in deep operations, and have poor corrosion resistance, aging and stability.

Method used

A heat-resistant and freezing-resistant water-based permeable inorganic waterproofing agent is adopted, and its formulation includes active potassium silicate, silicate cement, modified silica, filler, coupling agent, catalyst, dispersant and stabilizer. Adhesion and pore filling effect are enhanced by the combined action of the surface treatment of the modified silica and the specific dispersant composition.

Benefits of technology

It significantly improves the waterproofing performance, corrosion resistance, aging and stability of the waterproofing agent, meets the construction needs of deep operations, and has excellent comprehensive performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the field of concrete additives, in particular to a heat-resistant anti-freezing water-based permeable inorganic waterproof agent as well as a preparation method and application thereof. The invention discloses a heat-resistant and anti-freezing water-based permeable inorganic waterproof agent which is prepared from the following raw materials in parts by mass: 55-70 parts of active potassium silicate, 10-12 parts of Portland cement, 10-20 parts of modified silicon dioxide, 5-10 parts of a filling agent, 2-4 parts of a coupling agent, 0.5-1.5 parts of a catalyst, 3-8 parts of a dispersing agent, 1.5-3 parts of a stabilizer and 30-50 parts of deionized water. The inorganic waterproof agent prepared by the invention not only has excellent waterproof performance, but also can effectively improve the corrosion resistance, aging resistance, stability and the like of concrete at the same time, can meet the construction requirements of existing deep operation, has very excellent comprehensive performance, and has very excellent application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of concrete additives, and in particular to a heat-resistant and frost-resistant aqueous penetrating inorganic waterproofing agent and a preparation method and application thereof. Background Art

[0002] In modern buildings and infrastructure construction, concrete is one of the most commonly used materials. However, ordinary concrete has many defects, such as susceptibility to moisture erosion, carbonization, freeze-thaw cycle damage, etc., which seriously affect the service life and service quality of concrete structures. In order to overcome these shortcomings, the traditional practice is to lay rolls or apply other types of waterproof layers on the concrete surface, but this method is easily affected by external factors, such as aging, mechanical damage, etc., resulting in a short-lasting waterproof effect.

[0003] In recent years, with the increasing emphasis on the durability of buildings and infrastructure, a new waterproofing solution has been developed: water-based penetrating inorganic waterproofing agents. This type of waterproofing agent is based on alkali metal silicate solutions and has catalysts and other additives. It can be sprayed directly on the surface of concrete and quickly penetrate deep into the interior. Under the action of the catalyst, it reacts chemically with the free alkali substances in the concrete to form inert crystals. These crystals not only fill the pores and microcracks inside the concrete, but also form a closed waterproof barrier, effectively preventing the intrusion of moisture and other harmful substances.

[0004] Although existing water-based penetrating inorganic waterproofing agents have significantly improved the waterproof performance of concrete, they still face some challenges in practical applications. For example, the penetration depth needs to be improved. The penetration depth of some products limits their application in operations that require deep layers, and they are not effective in repairing deep cracks or larger pores. In certain specific environments (such as extreme climatic conditions), the adaptability and stability of the product may be affected, and problems such as poor corrosion resistance, aging resistance and stability may occur in long-term use.

[0005] Therefore, in order to solve the above problems, the present application provides a heat-resistant and frost-resistant aqueous penetrating inorganic waterproofing agent and a preparation method thereof. The inorganic waterproofing agent prepared in the present application not only has excellent waterproof performance, but also can effectively improve the corrosion resistance, aging and stability of concrete. It can meet the existing deep operation construction needs, has excellent comprehensive performance, and has excellent application prospects. Summary of the invention

[0006] In order to solve the above problems, the first aspect of the present application provides a heat-resistant and frost-resistant aqueous penetrating inorganic waterproofing agent. The raw materials are, by mass: 55 to 70 parts of active potassium silicate, 10 to 12 parts of silicate cement, 10 to 20 parts of modified silica, 5 to 10 parts of filler, 2 to 4 parts of coupling agent, 0.5 to 1.5 parts of catalyst, 3 to 8 parts of dispersant, 1.5 to 3 parts of stabilizer, and 30 to 50 parts of deionized water.

[0007] As a preferred solution, the modulus of the active potassium silicate is 1-3.

[0008] As a preferred solution, the modulus of the active potassium silicate is 2 to 2.5.

[0009] As a preferred solution, the solid content of the active potassium silicate is 20-40%.

[0010] As a preferred solution, the solid content of the active potassium silicate is 25-35%.

[0011] As a preferred solution, the silicate cement is ordinary silicate cement or early strength silicate cement.

[0012] As a preferred solution, the strength grade of the silicate cement is 32.5 or 42.5.

[0013] As a preferred scheme, the preparation method of the modified silica specifically includes the following steps: S1: adding silica and aluminum chloride to deionized water, adding glutaric anhydride and tetraisopropyl titanate, heating to 70-75°C and keeping warm for 2-2.5 hours; S2: after S1 is completed, continue to add DMF solution of terephthalic acid and p-aminobenzoic acid, stir and mix completely, heat to 100-110°C, keep warm for reaction for 14-16 hours, and after completion, naturally cool the product to room temperature, wash it alternately with DMF and anhydrous ethanol 2-3 times, and dry it to obtain pretreated particles; S3: mixing the pretreated particles with zinc nitrate and 2-methylimidazole, adding them to the DMF solution, and then heating to 60-80°C and keeping warm for 5-6 hours. After the reaction is completed, add triethanolamine to adjust the pH value to 7.5-8, and then wash the product alternately with acetone and deionized water 2-3 times, and dry it in a vacuum at 70-80°C to obtain.

[0014] As a preferred solution, the mass ratio of silicon dioxide, aluminum chloride glutaric anhydride and tetraisopropyl titanate is (1-1.2): (2.5-3): (0.6-0.8): (0.1-0.2).

[0015] As a preferred solution, the mass ratio of aluminum chloride, terephthalic acid and p-aminobenzoic acid is (2.5-3): (1.5-1.6): (0.4-0.6).

[0016] As a preferred solution, the mass ratio of zinc nitrate and 2-methylimidazole in the pretreated particles is (1.5-1.8): (0.8-1.2): (0.6-1).

[0017] As a preferred solution, the average particle size of the silicon dioxide is 10-20 nm; the average particle size of the modified silicon dioxide is 600-700 nm.

[0018] By adding the above-mentioned modified silica in this application, not only the waterproof performance of the inorganic waterproofing agent is effectively improved, but also its corrosion resistance, aging and stability can be effectively improved at the same time, effectively meeting the needs of existing construction operations. The prepared modified silica can produce a good coordination effect with the site particles in the framework structure through the multi-carboxyl groups after surface treatment, and then realize the embedding of silica on the surface while the framework is formed, and because a relatively excessive amount of silica is added, the actual final structure formed is a complex structure of the surface embedding package of silica, and the existence of this structure can effectively improve the waterproofing agent after crystallization, for the filling effect of the concrete system pores, and through the strong carboxyl connection effect, it can greatly improve its penetration depth on the concrete surface; and after the penetration is completed, it can also enhance the adhesion of the modified particles in the pores through the joint action with the specific dispersant composition in this application, avoiding the fluctuation and migration phenomenon of a large number of particles in the micropores of concrete, and then effectively reduce the number of surface cracks during long-term use, so as to obtain excellent waterproof performance.

[0019] On the other hand, the composite particle structure formed by the intercalation can greatly enhance its connection with the active potassium silicate, and thus ensure the stability of the crystal particles in the micropores in more severe use environments. The modified silica can serve as a fixed site to avoid excessive traction on the internal particles due to high heat, high cold and high humidity environments. The added dispersant can form a multi-layer structural film on the surface of the particles after the use of the waterproofing agent, thereby greatly limiting the frequency of particle migration activities after stabilization. The smoother structural membrane surface also helps reduce surface cracks, thereby enabling the concrete material to obtain excellent corrosion resistance, aging and stability performance.

[0020] As a preferred solution, the filler is a composition of bentonite, calcium chloride and hydroxyethyl cellulose.

[0021] As a preferred solution, the mass ratio of bentonite, calcium chloride and hydroxyethyl cellulose is (5-8):(2-3):(1-2).

[0022] As a preferred solution, the mass ratio of bentonite, calcium chloride and hydroxyethyl cellulose is (5.5-6.5):(2-2.5):(1.2-1.6).

[0023] As a preferred solution, the bentonite is lithium-based bentonite.

[0024] As a preferred solution, the coupling agent is at least one of a titanate coupling agent or an organosilicon coupling agent.

[0025] As a preferred solution, the coupling agent is an aminosilane coupling agent.

[0026] As a preferred solution, the aminosilane coupling agent is 3-aminopropyltriethoxysilane.

[0027] As a preferred solution, the catalyst is at least one of tetrabutyl titanate, ethyl titanate, isopropyl titanate and tri-n-butyl aluminate.

[0028] As a preferred solution, the catalyst is tetrabutyl titanate.

[0029] As a preferred solution, the dispersant is a composition of polycarboxylate, polydimethylsiloxane-polyethylene oxide block copolymer and fatty alcohol polyoxyethylene ether.

[0030] As a preferred solution, the mass ratio of the polycarboxylate, the polydimethylsiloxane-polyethylene oxide block copolymer and the fatty alcohol polyoxyethylene ether is (4-6): (1.5-2): (0.5-1).

[0031] As a preferred solution, the mass ratio of the polycarboxylate, the polydimethylsiloxane-polyethylene oxide block copolymer and the fatty alcohol polyoxyethylene ether is (4.5-5): (1.6-1.8): (0.7-0.9).

[0032] As a preferred solution, the fatty alcohol polyoxyethylene ether is isomeric C12~13 fatty alcohol polyoxyethylene ether.

[0033] As a preferred solution, the hydroxyl value of the isomeric C12-13 fatty alcohol polyoxyethylene ether is 120-150 mgKOH / g.

[0034] As a preferred solution, the stabilizer is a combination of sodium molybdate, sodium nitrite and zinc phosphate.

[0035] As a preferred solution, the mass ratio of sodium molybdate, sodium nitrite and zinc phosphate is (4-6): (1-2): (0.5-1).

[0036] As a preferred solution, the mass ratio of sodium molybdate, sodium nitrite and zinc phosphate is (4.5-5.5):(1.2-1.6):(0.6-0.8).

[0037] The second aspect of the present application provides a method for preparing the above-mentioned heat-resistant and frost-resistant aqueous penetrating inorganic waterproofing agent, which specifically includes the following steps: S1: adding active potassium silicate, silicate cement, modified silica and filler in a mixing container containing deionized water in sequence, and continuously stirring at 100-140 rpm until mixed evenly to obtain a mixture; S2: slowly adding a coupling agent, a dispersant and a stabilizer to the mixture, and continuing to stir at 100-140 rpm for 15-25 minutes to ensure that the components are fully dissolved and evenly dispersed; S3: finally adding a catalyst, increasing the speed to 200-240 rpm and vigorously stirring for about 10-20 minutes to completely fuse all the components to form a uniform suspension, and then letting the product stand overnight, and after the bubbles are completely eliminated, transferring it to a sealed container and sealing it to obtain the product.

[0038] The third aspect of the present application provides an application of the above-mentioned heat-resistant and frost-resistant aqueous penetrating inorganic waterproofing agent in underground structures, water conservancy projects, residential buildings, marine engineering and bridges and roads.

[0039] The beneficial effects of this application are: 1. The heat-resistant and frost-resistant aqueous penetrating inorganic waterproofing agent provided in the present application not only has excellent waterproof performance, but also can effectively improve the corrosion resistance, aging and stability of concrete, etc., can meet the existing deep operation construction needs, has very excellent comprehensive performance, and has excellent application prospects. 2. A heat-resistant and frost-resistant aqueous penetrating inorganic waterproofing agent provided in the present application, the added modified silica can produce a good coordination effect with the site particles in the framework structure through the multi-carboxyl groups after surface treatment, thereby realizing the embedding of silica on the surface while the framework is formed, and because a relatively excessive amount of silica is added, the actual final structure formed is a complex structure of surface embedding and wrapping of silica, the existence of which can effectively improve the filling effect of the waterproofing agent on the pores of the concrete system after crystallization, thereby ultimately obtaining good waterproof performance. 3. A heat-resistant and frost-resistant aqueous penetrating inorganic waterproofing agent provided in the present application, wherein the added modified silica, through the joint action with a specific dispersant composition, enhances the adhesion of the modified particles in the pores, thereby avoiding the fluctuation and migration of a large number of particles in the micropores of concrete, and thus effectively reducing the number of surface cracks during long-term use. On the other hand, the dispersant can form a multi-layer structural film on the surface of the particles after the use of the waterproofing agent, thereby greatly limiting the frequency of the migration activities of the particles after stabilization, and the smoother structural film surface also helps to reduce surface cracks, thereby enabling the concrete material to obtain excellent corrosion resistance, aging and stability performance. DETAILED DESCRIPTION The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.

[0040] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.

[0041] Example 1 Example 1 The first aspect provides a heat-resistant and frost-resistant aqueous penetrating inorganic waterproofing agent, the raw materials of which are, by mass: 62.4 parts of active potassium silicate, 10.8 parts of silicate cement, 14.6 parts of modified silica, 8.8 parts of filler, 2.9 parts of coupling agent, 0.8 parts of catalyst, 6.5 parts of dispersant, 2.1 parts of stabilizer, and 42.8 parts of deionized water.

[0042] The active potassium silicate has a modulus of 2 and a solid content of 30%, and was purchased from Jinan Quanxing New Materials Co., Ltd., China.

[0043] The silicate cement was ordinary silicate cement with a strength grade of 42.5, purchased from Hebei McMahon Mineral Products Co., Ltd., China.

[0044] The preparation method of modified silicon dioxide specifically comprises the following steps, calculated by mass: S1: 1.1 parts of silicon dioxide and 2.8 parts of aluminum chloride are mixed and added to 120 parts of deionized water, 0.68 parts of glutaric anhydride and 0.12 parts of tetraisopropyl titanate are added, and the temperature is raised to 70°C and kept warm for 2 hours; S2: after S1 is completed, a DMF solution containing 1.55 parts of terephthalic acid and 0.56 parts of p-aminobenzoic acid (a total of 60 parts) is added, and the mixture is stirred and mixed thoroughly, and the temperature is raised to 110°C and kept warm for 2 hours. The mixture was reacted at room temperature for 15 hours. After completion, the product was naturally cooled to room temperature, washed alternately with DMF and anhydrous ethanol for 3 times, and dried to obtain pretreated particles; S3: 1.6 parts of pretreated particles were mixed with 1.1 parts of zinc nitrate and 0.74 parts of 2-methylimidazole and added to 100 parts of DMF solution, and then the temperature was raised to 75°C and kept warm for 5.5 hours. After the reaction was completed, triethanolamine was added to adjust the pH value to 8. The product was then washed alternately with acetone and deionized water for 3 times, and dried in a vacuum oven at 75°C to obtain the product.

[0045] The average particle size of silica is 16 nm; the average particle size of modified silica is 668 nm.

[0046] The filler is a composition of lithium bentonite, calcium chloride and hydroxyethyl cellulose, and the mass ratio of the three is 6:2.2:1.3.

[0047] The coupling agent is 3-aminopropyltriethoxysilane.

[0048] The catalyst is tetrabutyl titanate.

[0049] The dispersant is a composition of polycarboxylate, polydimethylsiloxane-polyethylene oxide block copolymer and isomeric C13 fatty alcohol polyoxyethylene ether, and the mass ratio of the three is 4.8:1.6:0.8.

[0050] The isomeric C13 fatty alcohol polyoxyethylene ether has a hydroxyl value of 120 mgKOH / g and was purchased from the E-1306 model product sold by Haian Guoyun Chemical in China.

[0051] Polycarboxylates were purchased from Polycarboxylate Dispersant 5040 sold by Wuhan Huaxiang Kejie Biotechnology Co., Ltd., China.

[0052] The polydimethylsiloxane-polyethylene oxide block copolymer is DC-5700 sold by Dow Corning of the United States.

[0053] The stabilizer is a combination of sodium molybdate, sodium nitrite and zinc phosphate, and the mass ratio of the three is 5.2:1.5:0.8.

[0054] The second aspect of the present embodiment provides a method for preparing the above-mentioned heat-resistant and antifreeze water-based penetrating inorganic waterproofing agent, which specifically includes the following steps: S1: adding active potassium silicate, silicate cement, modified silica and filler to a mixing container containing deionized water in sequence, and continuously stirring at 100-140 rpm until mixed evenly to obtain a mixture; S2: slowly adding a coupling agent, a dispersant and a stabilizer to the mixture, and continuing to stir at 100-140 rpm for 15-25 min to ensure that the components are fully dissolved and evenly dispersed; S3: finally adding a catalyst, increasing the speed to 200-240 rpm and vigorously stirring for about 10-20 min to completely fuse all the components to form a uniform suspension, and then letting the product stand overnight, and after the bubbles are completely eliminated, transferring it to a sealed container and sealing it to obtain the product.

[0055] Example 2 The specific implementation method of this embodiment is basically the same as that of Example 1, except that: the raw materials of the heat-resistant and frost-resistant aqueous penetrating inorganic waterproofing agent, in parts by mass, are: 68.5 parts of active potassium silicate, 11.6 parts of silicate cement, 18.5 parts of modified silicon dioxide, 6.5 parts of filler, 3.4 parts of coupling agent, 1.1 parts of catalyst, 7.5 parts of dispersant, 2.1 parts of stabilizer, and 44.5 parts of deionized water.

[0056] The filler is a composition of lithium bentonite, calcium chloride and hydroxyethyl cellulose, and the mass ratio of the three is 5.5:3:2.

[0057] The dispersant is a composition of polycarboxylate, polydimethylsiloxane-polyethylene oxide block copolymer and isomeric C13 fatty alcohol polyoxyethylene ether, and the mass ratio of the three is 5.6:2:0.5.

[0058] The stabilizer is a combination of sodium molybdate, sodium nitrite and zinc phosphate, and the mass ratio of the three is 4.2:2:0.6.

[0059] Example 3 The specific implementation of this embodiment is basically the same as that of Example 1, except that: the raw materials of the heat-resistant and frost-resistant aqueous penetrating inorganic waterproofing agent, in parts by mass, are: 59.6 parts of active potassium silicate, 10.1 parts of silicate cement, 11.2 parts of modified silica, 5.2 parts of filler, 2.2 parts of coupling agent, 0.6 parts of catalyst, 4.8 parts of dispersant, 1.6 parts of stabilizer, and 40.8 parts of deionized water.

[0060] The filler is a composition of lithium bentonite, calcium chloride and hydroxyethyl cellulose, and the mass ratio of the three is 8:2:1.

[0061] The dispersant is a composition of polycarboxylate, polydimethylsiloxane-polyethylene oxide block copolymer and isomeric C13 fatty alcohol polyoxyethylene ether, and the mass ratio of the three is 4.4:1.5:0.9.

[0062] The stabilizer is a combination of sodium molybdate, sodium nitrite and zinc phosphate, and the mass ratio of the three is 5.8:1.1:0.9.

[0063] Comparative Example 1 The specific implementation of this comparative example is basically the same as that of Example 1, except that the filler is a composition of lithium bentonite, calcium chloride and hydroxyethyl cellulose, and the mass ratio of the three is 2:5:0.2.

[0064] Comparative Example 2 The specific implementation of this comparative example is basically the same as that of Example 1, except that the dispersant is a composition of polycarboxylate, polydimethylsiloxane-polyethylene oxide block copolymer and isomeric C13 fatty alcohol polyoxyethylene ether, and the mass ratio of the three is 1:1:3.

[0065] Comparative Example 3 The specific implementation of this comparative example is basically the same as that of Example 1, except that the dispersant is a composition of polycarboxylate, polydimethylsiloxane-polyethylene oxide block copolymer and isomeric C13 fatty alcohol polyoxyethylene ether, and the mass ratio of the three is 8:0.5:0.2.

[0066] Comparative Example 4 The specific implementation of this comparative example is basically the same as that of Example 1, except that the stabilizer is a combination of sodium molybdate, sodium nitrite and zinc phosphate, and the mass ratio of the three is 6:0.5:0.1.

[0067] Comparative Example 5 The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of modified silicon dioxide specifically comprises the following steps, calculated by mass: S1: 0.4 parts of silicon dioxide and 3.9 parts of aluminum chloride are mixed and added to 120 parts of deionized water, 0.42 parts of glutaric anhydride and 0.05 parts of tetraisopropyl titanate are added, and the temperature is raised to 70°C and kept warm for 2 hours; S2: after S1 is completed, a DMF solution containing 1.85 parts of terephthalic acid and 0.24 parts of p-aminobenzoic acid (a total of 60 parts) is added, and stirred. After the mixing is complete, the temperature is raised to 110°C and the reaction is kept warm for 15 hours. After completion, the product is naturally cooled to room temperature, washed alternately with DMF and anhydrous ethanol for 3 times, and dried to obtain pretreated particles; S3: 1.6 parts of pretreated particles are mixed with 1.1 parts of zinc nitrate and 0.74 parts of 2-methylimidazole and added to 100 parts of DMF solution, and then the temperature is raised to 75°C and kept warm for 5.5 hours. After the reaction is completed, triethanolamine is added to adjust the pH value to 8, and then the product is washed alternately with acetone and deionized water for 3 times, and vacuum dried at 75°C to obtain.

[0068] The average particle size of the modified silica was 554 nm.

[0069] Comparative Example 6 The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of modified silicon dioxide specifically comprises the following steps, calculated by mass: S1: 2.1 parts of silicon dioxide and 3.4 parts of aluminum chloride are mixed and added to 120 parts of deionized water, 0.68 parts of glutaric anhydride and 0.12 parts of tetraisopropyl titanate are added, and the temperature is raised to 70°C and kept warm for 2 hours; S2: after S1 is completed, a DMF solution containing 1.55 parts of terephthalic acid and 0.56 parts of p-aminobenzoic acid (a total of 60 parts) is added, and stirred. After the mixing is complete, the temperature is raised to 110°C and the reaction is kept warm for 15 hours. After completion, the product is naturally cooled to room temperature, washed alternately with DMF and anhydrous ethanol for 3 times, and dried to obtain pretreated particles; S3: 2.8 parts of pretreated particles are mixed with 0.8 parts of zinc nitrate and 0.54 parts of 2-methylimidazole and added to 100 parts of DMF solution, and then the temperature is raised to 75°C and kept warm for 5.5 hours. After the reaction is completed, triethanolamine is added to adjust the pH value to 8, and then the product is washed alternately with acetone and deionized water for 3 times, and vacuum dried at 75°C to obtain.

[0070] The average particle size of the modified silica is 729 nm.

[0071] Comparative Example 7 The specific implementation of this comparative example is basically the same as that of Example 1, except that the average particle size of silicon dioxide is 35 nm; the average particle size of modified silicon dioxide is 821 nm.

[0072] Performance Evaluation Permeability test: The inorganic waterproofing agent prepared in the embodiment and the comparative example was tested for permeability according to the reference standard JC / T 1018-2020. The test value was the average value of 10 tests and recorded in Table 1.

[0073] Waterproofness test: The inorganic waterproofing agent prepared in the embodiment and the comparative example was tested for surface hydrophilicity and hydrophobicity according to the reference standard JC / T 1018-2020. The surface water contact angle was tested by the sessile drop method. The water drop size was 5 μL. The test time was 30 s. The test value was the average of 10 tests and recorded in Table 1.

[0074] Temperature stability test: The inorganic waterproofing agent obtained in the embodiment and the comparative example was tested for temperature stability according to the reference standard JC / T 1018-2020, and the low temperature environment and the high temperature environment were tested respectively; low temperature test conditions: 20~-20℃, 15 times; high temperature test conditions: 160℃; if the product does not show surface powdering, cracking or damage under both low temperature and high temperature environment tests, it is qualified, otherwise it is unqualified; 50 groups of samples are tested in each group, and the qualified rate results are recorded in Table 1.

[0075] Corrosion resistance test: The inorganic waterproofing agent prepared in the embodiment and the comparative example was tested for alkali corrosion resistance according to the reference standard JC / T 1018-2020. The test solution was a saturated calcium hydroxide solution. The test time was 250 hours. After the test was completed, if there was no surface powdering, cracking or damage, it was considered qualified, otherwise it was considered unqualified. 50 groups of samples were tested in each group, and the qualified rate results were recorded in Table 1.

[0076] Table 1 Performance test results It can be seen from the examples and comparative examples of the present application and the data results in Table 1 that Examples 1 to 3 of the present application have obvious advantages over comparative examples 1 to 7 in terms of impermeability, water resistance, temperature stability and corrosion resistance and aging performance. This is mainly due to the combined effect of the modified silica particles, the special dispersant composition, the stabilizer composition and other matching technical solutions specified in the present application. Comparative examples 1 to 7 did not adopt the technical solution specified in the present application, resulting in obvious disadvantages in the above-mentioned performance tests, which further proves the necessity of the technical solution specified in the present application for the technical effect of the present application and solving technical problems.

Claims

1. A heat-resistant and frost-resistant aqueous penetrating inorganic waterproofing agent, characterized in that: The raw materials are as follows: 55-70 parts of active potassium silicate, 10-12 parts of silicate cement, 10-20 parts of modified silicon dioxide, 5-10 parts of filler, 2-4 parts of coupling agent, 0.5-1.5 parts of catalyst, 3-8 parts of dispersant, 1.5-3 parts of stabilizer, and 30-50 parts of deionized water. The modulus of the active potassium silicate is 1 to 3; The solid content of the active potassium silicate is 20-40%; The silicate cement is ordinary silicate cement or early strength silicate cement; The strength grade of the silicate cement is 32.5 or 42.5; The preparation method of the modified silica specifically includes the following steps: S1: adding silica and aluminum chloride to deionized water, adding glutaric anhydride and tetraisopropyl titanate, heating to 70-75°C and keeping warm for 2-2.5 hours; S2: after S1 is completed, continue to add DMF solution of terephthalic acid and p-aminobenzoic acid, stir and mix thoroughly, heat to 100-110°C, keep warm for 14-16 hours, and after completion, naturally cool the product to room temperature, wash alternately with DMF and anhydrous ethanol 2-3 times, and dry to obtain pretreated particles; S3: mixing the pretreated particles with zinc nitrate and 2-methylimidazole, adding to the DMF solution, and then heating to 60-80°C and keeping warm for 5-6 hours. After the reaction is completed, add triethanolamine to adjust the pH value to 7.5-8, and then wash the product alternately with acetone and deionized water 2-3 times, and dry it in a vacuum at 70-80°C to obtain; The mass ratio of aluminum chloride, terephthalic acid and p-aminobenzoic acid is (2.5-3): (1.5-1.6): (0.4-0.6); The mass ratio of the pretreated particles, zinc nitrate and 2-methylimidazole is (1.5-1.8): (0.8-1.2): (0.6-1).

2. The heat-resistant and antifreeze aqueous penetrating inorganic waterproofing agent according to claim 1, characterized in that: The filler is a composition of bentonite, calcium chloride and hydroxyethyl cellulose; the mass ratio of the bentonite, calcium chloride and hydroxyethyl cellulose is (5-8):(2-3):(1-2).

3. The heat-resistant and antifreeze aqueous penetrating inorganic waterproofing agent according to claim 2, characterized in that: The average particle size of the silicon dioxide is 10-20 nm; the average particle size of the modified silicon dioxide is 600-700 nm.

4. The heat-resistant and antifreeze aqueous penetrating inorganic waterproofing agent according to claim 3, characterized in that: The coupling agent is at least one of a titanate coupling agent and an organosilicon coupling agent.

5. The heat-resistant and antifreeze aqueous penetrating inorganic waterproofing agent according to claim 4, characterized in that: The coupling agent is an aminosilane coupling agent.

6. The heat-resistant and antifreeze aqueous penetrating inorganic waterproofing agent according to claim 5, characterized in that: The catalyst is at least one of tetrabutyl titanate, ethyl titanate, isopropyl titanate and tri-n-butyl aluminate.

7. The heat-resistant and antifreeze aqueous penetrating inorganic waterproofing agent according to claim 6, characterized in that: The dispersant is a composition of polycarboxylate, polydimethylsiloxane-polyethylene oxide block copolymer and fatty alcohol polyoxyethylene ether; the mass ratio of the polycarboxylate, polydimethylsiloxane-polyethylene oxide block copolymer and fatty alcohol polyoxyethylene ether is (4-6): (1.5-2): (0.5-1).

8. The heat-resistant and antifreeze aqueous penetrating inorganic waterproofing agent according to claim 7, characterized in that: The stabilizer is a composition of sodium molybdate, sodium nitrite and zinc phosphate; the mass ratio of the sodium molybdate, sodium nitrite and zinc phosphate is (4-6): (1-2): (0.5-1).

9. A method for preparing the heat-resistant and antifreeze aqueous penetrating inorganic waterproofing agent according to any one of claims 1 to 8, characterized in that: The specific steps include: S1: Add active potassium silicate, silicate cement, modified silica and filler to a mixing container containing deionized water in sequence, and continue stirring at 100-140 rpm until mixed evenly to obtain a mixture; S2: Slowly add coupling agent, dispersant and stabilizer to the mixture, and continue stirring at 100-140 rpm for 15-25 min to ensure that the components are fully dissolved and evenly dispersed; S3: Finally, add the catalyst, increase the speed to 200-240 rpm and stir vigorously for about 10-20 min to completely blend all the components to form a uniform suspension, then let the product stand overnight, and transfer it to a sealed container and seal it after the bubbles are completely eliminated.

10. Use of the heat-resistant and frost-resistant aqueous penetrating inorganic waterproofing agent according to any one of claims 1 to 8 in underground structures, water conservancy projects, residential buildings, marine projects, and bridges and roads.

Citation Information

Patent Citations

  • Inorganic silicate waterproof agent with depth permeability and filling property and preparation method of waterproof agent

    CN104844269A

  • Self-healing inorganic nano waterproof liquid and preparation method thereof

    CN113480228A

  • Concrete internal doping type self-repairing waterproof agent

    CN115417619A

  • Special environment-friendly high-corrosion-resistance zinc-aluminum coating for metal components and preparation method thereof

    CN118813123A

  • Penetrative silicate waterproof agents with hydrophilic fiber reinforcement having antibacterial activities and waterproofing methods using the same

    KR102058546B1

Cited By

  • Water-based permeable inorganic waterproof agent and preparation method thereof

    CN122464635A

  • A water-based penetrating inorganic waterproofing agent and a preparation method thereof

    CN122464635B